PENINGKATAN KETERAMPILANMOTORIK KASAR SISWA MELALUI SENAM IRAMA DI KELAS I SD 1501 HURUNG JILOK - Nurhayati Siregar; Irma Sari Daulay; Netti Hasibuan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Based on the results of the study it can be concluded that the improvement of students' gross motor skills through rhythmic gymnastics in class I SD Negeri 1501 Hurung Jilok obtained the percentage of completeness of gross motor skills of students in the complete category of 7 students or 30.43%, while the completeness of gross motor skills of students in the category of not yet complete 16 students or 69.57%, while the first cycle obtained the percentage of complete gross motor skills of students in the complete category of 13 students or 56.52%, while the complete gross motor skills of students in the incomplete category were 10 students or 43.48% and for cycle II it was obtained that the percentage of completeness of gross motor skills of students in the complete category was 21 students or 91.30%, while the completeness of gross motor skills of students in the incomplete category was 2 students or 8.70%. So it can be concluded that through rhythmic gymnastics that is applied it can improve the gross motor skills of students in class I SD Negeri 1501 Hurung Jilok.